Starter culture in pate amazonian painted (Pseudoplatystoma fasciatum x Leiarius marmoratus): Development and determination of commercial term (Research, Society and Development, 2023)
The present study aimed to prepare an Amazonian painted pâté added with starter culture (Staphylococcus xylosus and Pediococcus pensasaceus), carry out its characterization and determine the commercial deadline and develop a predictive mathematical model to verify the growth of the culture. The pâté was prepared with cooked fish and starter culture. Physicochemical and microbiological analyzes were carried out on the pâté, which was stored in plastic and glass packaging for 24 days at 10°C. The pâté presented moisture, ash, proteins, lipids and color parameters (close to white, red and yellow) contents, stable during storage and sanitary evaluation within legal standards. Product pH decreased over time (from 6.43 to 5.11), while total volatile bases and lipid oxidation increased (from 8.81 to 10.36 mgN/100g and from 0.35 to 0. 52 MDA/Kg, respectively). Mesophilic bacteria increased (from 6.66 to 9.25 log CFU/g), while psychrotrophic bacteria and Pseudomonas sp showed limited growth (4.79 and 0 log CFU/g, respectively). The bacteria in the starter culture showed good development (from 6.51 and 6.57 log CFU/g to 9.32 and 9.12 log CFU/g) and showed exponential growth after a short adaptation phase, as modeled by the Gompertz model. Based on these results, the commercial deadline was established at 15 days, concluding that developing a fish pâté added with starter culture will provide the consumer with attractive characteristics.